2010
DOI: 10.1080/10408390903467480
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Dietary Habits in Adolescents

Abstract: Lifestyle plays an important role in the development of obesity during childhood and adolescence. We provide up-to-date information about the relationship between obesity and food intake and dietary patterns in adolescents. Scientific evidence is increasing about the dietary factors associated with this relationship, specifically a low meal frequency, skipping breakfast, and a high consumption of sugar sweetened beverages. Maybe some of the reviewed dietary factors could cluster in the same population of adole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
139
0
30

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(176 citation statements)
references
References 68 publications
7
139
0
30
Order By: Relevance
“…Investigating eating behaviours in children longitudinally during the transition into adolescence is recommended in order to provide important information on when, how and why dietary changes occur (2,6,12,13) . This will in turn enable the development of strategies for interventions (14,15) and then further influence future health.…”
mentioning
confidence: 99%
“…Investigating eating behaviours in children longitudinally during the transition into adolescence is recommended in order to provide important information on when, how and why dietary changes occur (2,6,12,13) . This will in turn enable the development of strategies for interventions (14,15) and then further influence future health.…”
mentioning
confidence: 99%
“…A recently published study among Norwegian children showed increased odds of being overweight when fewer than four meals were eaten the previous day (11) . Second, studies from the 1980s to today have described a distinct change in meal pattern in children and adolescents, more than observed in the adult population (2,3,12) . These changes vary widely from one region to the other (12) .…”
mentioning
confidence: 99%
“…In Norway it has been reported that 15 % of healthy children and adolescents skip breakfast and 30 % skip lunch twice weekly or more (13) . In the USA the prominent trend is an increase in snacking events between meals (12) . A third focus on meal pattern has concerned the importance of how and with whom meals are eaten.…”
mentioning
confidence: 99%
“…Independently of these characteristics, both periods are crucial in regard to growth and development and both children and adolescents can acquire and/or modify those eating habits which are associated with excess weight. 8 Various authors coincide in the definition of eating habits as a set of customs and repetitive manifestations which condition the way individuals consume food, and are based directly or indirectly on sociocultural practices. 9,10 Feeding behavior is a complex phenomenon, based on political, economic, social and cultural conditioning factors.…”
Section: Introductionmentioning
confidence: 99%